Relationship between Sustainable Development Goals and Media and Information Literacy - Cuevas Salvador, Jesús (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Given the problem of lack of interest, commitment and understanding of sustainable development, didactic innovation has been integrated into the university classroom, through the action research methodology. Through the general objective, to apply media and information literacy (AMI) skills for the understanding and scope of the 2030 Agenda, in the Master's Degree in Teaching, during the 2021-2022 academic year, performance activities have been designed and implemented. The results indicate the impact of AMI only in 60% of the students. The conclusions discover the maker culture, the constructivist paradigm and communicate in multimedia, crossmedia and transmedia formats.